Small business scams: a preliminary overview and investigation - Weber, Paull; Schaper, Michael; Teo, Stephen; Geneste, Louis (International Council for Small Business, 2011)
This paper provides an overview of the current level of understanding about scams perpetrated against small businesses, and also reports on a preliminary study which highlights various forms of the phenomenon. A scam is a form of fraudulent, illegal activity that invites potential victims to accept an offer which leads to the loss of financial, organisational or personal resources. The limited research evidence available to date suggests that small businesses are particularly vulnerable to this type of criminal activity, are less likely to report such events, are likely to be subject to repeat attacks, and are particularly susceptible to online approaches. The ten cases reported in this paper are suggestive of a relatively high level of occurrence and a surprisingly high level of ignorance of the risks that these scams represent. A future research agenda is outlined.